Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper, 2012)
New commitments under PRGT-supported programs are expected to increase to about SDR 2 billion in 2012, in part reflecting the large ECF commitment (SDR 0.6 billion) for Bangladesh approved in April. Commitments in the first eight months of 2012 amounted to SDR 1.4 billion and a further SDR 0.6 billion is expected to be committed by year end. This compares to total commitments of SDR 1.2 billion in each of 2010 and 2011. If all elements of the 2009 financing package are secured, the PRGT will have an annual average lending capacity of SDR 2.2 billion remaining under this package for the period 2013-14. Additional.